Life Table Parameters of the Zoophytophagous Predator Brontocoris tabidus (Heteroptera: Pentatomidae) on Introduced and Native Plants - de Medeiros, Rômulo Sátiro; Vinha, Germano Lopes; Zanuncio, José Cola; Wilcken, Carlos Frederico [UNESP]; de Menezes, Claubert Wagner Guimarães; Soares, Marcus Alvarenga; Carvalho, Amélia Guimarães (Oxford University Press (OUP), 2019)
Brontocoris tabidus Signoret (Heteroptera: Pentatomidae) is a zoophytophagous predator of lepidopteran defoliators of eucalyptus in Brazil. This predator complements its diet with plants, which is fundamental for its population maintenance. The objective was to evaluate the B. tabidus development, reproduction, and life table parameters in the field on Eucalyptus cloeziana F. Muell. (T1), Psidium guajava Linn (Myrtales: Myrtaceae) (T2), or without plants (T3). The parameters estimated were: net reproductive rate (Ro); generation duration (DG); time for the population to double in size (TD); intrinsic population growth rate (rm), survival rate (lX), specific fertility (mx), life expectancy (ex), and mortality risk (qx). Ro, DG, TD, and rm were higher in the T1 and T2 than in T3. Plant presence favored the lx, mx, and qx. Ex values were 36.1 and 56.9 in the T3 and T1, respectively. The B. tabidus fertility, longevity, and life table parameters improvement on E. cloeziana and P. guajava plants are due to the water and nutrients obtained from them. B. tabidus can be reared with Tenebrio molitor Linnaeus (Coleoptara: Tenebrionidae) pupae on E. cloeziana or P. guajava plants in the field.
Keywords: Asopinae; Pentatomidae; predator; zoophytophagy